Synthesis and Characterization of Transition Metal Complexes of 12- and 14-Membered Tetraaza Macrocycles - Sangeetha, J.E.; Meenalochani, S.; Radha, K.; Chellappa, D. (Asian Journal of Chemistry, 2010)
Template synthesis of transition metal complexes with macrocyclic tetraaza (N4) ligands L' and L" [L' = 1,4,7,10- tetraazacyclododecane-2,3,8,9-tetraone and L" = 1,4,8,11- tetraazacyclotetradecane-2,3,9,10-tetraone have been described. The complexes were characterized by elemental analyses, molar conductance, magnetic susceptibility measurements, CV and electronic, IR, EPR spectral studies. On the basis of these studies Cu(II) complex has been assigned tetragonal geometry while other complexes are assigned octahedral geometry.